2017
DOI: 10.1093/ofid/ofx049
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Epidemiological Tool to Measure the Burden of Norovirus Infection and Disease in Resource-Limited Settings

Abstract: Background.Rapid, cost-effective tools are needed to estimate the disease burden of acute gastroenteritis (AGE) and norovirus (NoV) in resource-limited settings.Methods.Households with children (6 weeks–17 years) in rural Guatemala were randomly enrolled into 2 parallel AGE surveillance systems: (1) a prospective cohort, which included an enrollment visit followed by 1 year of prospective observation using a smartphone-based weekly symptom diary; and (2) 2 sequential cross-sectional rapid active sampling (RAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…This analysis was performed within a larger study 6 comparing two surveillance methodologies to estimate NoV and AGE disease burden in resource-limited settings. The first system, a prospective participatory syndromic surveillance (PSS) cohort, obtained baseline data and stool samples from participating households, and then prospectively followed them for AGE using a smartphone-based symptom diary application (Integra IT, Bogota, Colombia).…”
mentioning
confidence: 99%
“…This analysis was performed within a larger study 6 comparing two surveillance methodologies to estimate NoV and AGE disease burden in resource-limited settings. The first system, a prospective participatory syndromic surveillance (PSS) cohort, obtained baseline data and stool samples from participating households, and then prospectively followed them for AGE using a smartphone-based symptom diary application (Integra IT, Bogota, Colombia).…”
mentioning
confidence: 99%
“…The population suffers from high rates of food insecurity and child undernutrition, diarrheal disease, maternal depression, maternal and child morbidity, and mortality. 25 Recent studies have shown that the area is highly endemic for dengue, chikungunya, and ZIKV. 25,26 Research design.…”
Section: Settingmentioning
confidence: 99%
“…25 Recent studies have shown that the area is highly endemic for dengue, chikungunya, and ZIKV. 25,26 Research design. In 2017, we launched a prospective, natural history study of postnatally acquired ZIKV infection in infants and young children at the University of Colorado Center for Human Development research and clinic site in Guatemala.…”
Section: Settingmentioning
confidence: 99%
“…which, after enrollment and baseline sampling, children were monitored for AGE using a weekly smartphone-based symptom diary, with diagnostic testing performed for self-reported AGE (norovirus); or 2) two separate rapid active cross-sectional sampling (RAS) surveys conducted in October-November 2015 and January-February 2016 in which children in randomly selected households were screened for AGE symptoms in the previous week and tested for AGE regardless of a symptom report. 12 Randomization and enrollment of the households were conducted using a two-stage cluster sampling strategy in which 30 clusters of seven households each were enrolled in the PSS cohort and each of the two RAS cycles separately, as previously described. 12 Households in both arms received an information brochure about norovirus at the time of enrollment.…”
mentioning
confidence: 99%
“…12 Randomization and enrollment of the households were conducted using a two-stage cluster sampling strategy in which 30 clusters of seven households each were enrolled in the PSS cohort and each of the two RAS cycles separately, as previously described. 12 Households in both arms received an information brochure about norovirus at the time of enrollment. The vaccine knowledge and attitude survey was administered at the conclusion of this study, in September 2016.…”
mentioning
confidence: 99%